A novel role of protein tyrosine kinase2 in mediating chloride secretion in human airway epithelial cells. - Lihua Liang; Owen M Woodward; Zhaohui Chen; Robert Cotter; William B Guggino (PLoS ONE, 2011)
Ca(2+) activated Cl(-) channels (CaCC) are up-regulated in cystic fibrosis (CF) airway surface epithelia. The presence and functional properties of CaCC make it a possible therapeutic target to compensate for the deficiency of Cl(-) secretion in CF epithelia. CaCC is activated by an increase in cytosolic Ca(2+), which not only activates epithelial CaCCs, but also inhibits epithelial Na(+) hyperabsorption, which may also be beneficial in CF. Our previous study has shown that spiperone, a known antipsychotic drug, activates CaCCs and stimulates Cl(-) secretion in polarized human non-CF and CF airway epithelial cell monolayers in vitro, and in Cystic Fibrosis Transmembrane Conductance Regulator (CFTR) knockout mice in vivo. Spiperone activates CaCC not by acting in its well-known role as an antagonist of either 5-HT2 or D2 receptors, but through a protein tyrosine kinase-coupled phospholipase C-dependent pathway. Moreover, spiperone independently activates CFTR through a novel mechanism. Herein, we performed a mass spectrometry analysis and identified the signaling molecule that mediates the spiperone effect in activating chloride secretion through CaCC and CFTR. Proline-rich tyrosine kinase 2 (PYK2) is a non-receptor protein tyrosine kinase, which belongs to the focal adhesion kinase family. The inhibition of PYK2 notably reduced the ability of spiperone to increase intracellular Ca(2+) and Cl(-) secretion. In conclusion, we have identified the tyrosine kinase, PYK2, as the modulator, which plays a crucial role in the activation of CaCC and CFTR by spiperone. The identification of this novel role of PYK2 reveals a new signaling pathway in human airway epithelial cells.